Interpreting socio-cultural values in Toraja: The symbolism of Garonto’ Sura’ in Kada Tomina - Sendana, Aris Kaban; Rahman, Fathu; Nasmilah, Nasmilah; Sahib, Harlinah (Edelweiss Applied Science and Technology, 2025)
The interrelation of Toraja cultures is vividly embodied in the traditional motifs, garonto’ sura (the basic model of the engraving. It is the oldest one of the engravings), particularly in their engraving art, passura’. These motifs, prominently displayed on tongkonan (traditional houses) and rice barns, symbolize the socio-cultural values of the Toraja people. This study focuses on the expression of garonto’ sura in kada tomina (the words uttered by the Toraja traditional host. It is figurative language of the Toraja people used by the traditional host in both thanksgiving and burial rituals), verbal utterances by traditional hosts during high ceremonial events to interpret their symbolic representation of socio-cultural values. Employing a hermeneutic approach combined with communication semiotics, this research critically analyzes the meanings encoded in these motifs and their associated expressions. The motifs pa’sussu’, pa’tedong, and others are integral to Toraja rituals, such as rambu solo’ (death ceremony) and rambu tuka’ (thanksgiving ceremony). For example, pa’sussu’ symbolizes purity, nobility, and unity, while pa’tedong reflects the significance of the buffalo as a socio-economic and cultural icon. These motifs not only highlight social stratification but also reinforce the ideological and ceremonial practices of the Toraja people, illustrating their hierarchical structure and values such as leadership, respect, and community unity. Results reveal that kada tomina serves as a medium to convey these values, showcasing distinctions in language, rituals, and social practices. The study concludes that garonto’ sura expressions in kada tomina symbolize and perpetuate the Toraja’s cultural norms, hierarchy, and heritage, reinforcing the significance of traditional art and oration in preserving socio-cultural identity.